When diversity drops : race, religion, and affirmative action in higher education - Park, Julie J., 1982- (Rutgers University Press, 2013)
In this book, the author examines how losing racial diversity in a university affects the everyday lives of its students. She uses a student organization, the InterVarsity Christian Fellowship (IVCF) at "California University," as a case study to show how reductions in racial diversity impact the ability of students to sustain multiethnic communities.